Strategi Pengembangan Usaha Mikro, Kecil, dan Menengah (UMKM) Lokal Berbasis Platform Digital di Kota Malang - Ilyas, Taufiq Rahman (JOM, 2024)
This research maps the potential of local MSMEs based on digital platforms, looks for supporting and inhibiting factors and then plans actual strategies to adjust marketing needs. The research method used is descriptive research with a simple qualitative analysis approach. It is hoped that this research can contribute ideas to the community so that MSMEs in the city of Malang can further develop following the strategy formulation that we found. The digitalization strategy for MSMEs (Micro, Small and Medium Enterprises) is carried out to increase efficiency, productivity and market access for MSME players. Some MSME digitalization strategies that can be implemented are as follows; digital transformation to a digital ecosystem, information technology skills training, utilization of digital technology, digitalization development, investment in information technology infrastructure, use of digital platforms, and partnership collaboration.